2020
DOI: 10.1039/c9tc06145b
|View full text |Cite
|
Sign up to set email alerts
|

Sc3N@C80 and La@C82 doped graphene for a new class of optoelectronic devices

Abstract: Hybrid graphene photodetectors (PDs) with endohedral Sc3N@C80 and La@C82 were used by the Kaul Research Group at the University of North Texas to dope graphene p-type and n-type, respectively, that resulted in significant optoelectronic property enhancement of the PDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…The EQE of the hybrid GQDs/MoS 2 and the bare MoS 2 were calculated to be 241 and 14% at 400 nm, respectively, as shown in Figure d. As a result, we confirmed that the hybrid GQD/MoS 2 structure exhibits a higher photodetection capability than the bare MoS 2 device at 400 nm and over a broad wavelength range up to 1100 nm, with E g for the GQDs ∼2.5 eV. , Since the Fermi level E F of MoS 2 is lower than that of GQDs, electrons diffuse from the GQDs into MoS 2 , thus forming a built-in electric field at the hybrid GQD/MoS 2 interface. In their recent work, Li et al recorded an asymmetrical screening response from few layer graphene and MoS 2 .…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The EQE of the hybrid GQDs/MoS 2 and the bare MoS 2 were calculated to be 241 and 14% at 400 nm, respectively, as shown in Figure d. As a result, we confirmed that the hybrid GQD/MoS 2 structure exhibits a higher photodetection capability than the bare MoS 2 device at 400 nm and over a broad wavelength range up to 1100 nm, with E g for the GQDs ∼2.5 eV. , Since the Fermi level E F of MoS 2 is lower than that of GQDs, electrons diffuse from the GQDs into MoS 2 , thus forming a built-in electric field at the hybrid GQD/MoS 2 interface. In their recent work, Li et al recorded an asymmetrical screening response from few layer graphene and MoS 2 .…”
Section: Resultssupporting
confidence: 65%
“…Hybrid structures of MoS 2 integrated with other 2D materials are likely to show high quantum efficiency since the built-in field acting in ultrathin heterostructures over large contact areas causes the photogenerated electron–hole pairs to be separated more rapidly with a higher efficiency . At the same time, quantum dots (QDs) such as graphene (G-) QDs, PbS, PbSe, and CdTe integrated with 2D materials are reported to show very high gain and optical sensitivity in phototransistors due to the unique features of QDs. , …”
Section: Introductionmentioning
confidence: 99%
“…[182] These properties have been extended to additional graphitic derivatives, e.g. hybrid materials [183,184] and GQDs. [185,186]…”
Section: Optical and Optoelectronic Applicationsmentioning
confidence: 99%
“…Jayanand et al prepared PDs using two types of EMFs deposited on graphene via the electrophoretic method . The authors fabricated PDs using an EMF-deposited graphene channel (graphene/Sc 3 N@C 80 and graphene/La@C 82 ).…”
Section: Photodetectormentioning
confidence: 99%